2011
DOI: 10.1038/jp.2011.85
|View full text |Cite
|
Sign up to set email alerts
|

Possible counter effect in newborns of 1936A>G (I646V) polymorphism in the AKAP10 gene encoding A-kinase-anchoring protein 10

Abstract: Objective: Cyclic adenosine monophosphate/protein kinase A (PKA) is important in embryonic development. The human AKAP10 gene is polymorphic: 1936A>G results in changes to a PKA-binding domain and increased targeting to mitochondria. Previous studies found G1936 as 'deleterious' in adults, and this study investigates whether this holds true in preterm birth.Study Design: Study group consisted of 80 preterm newborns (PTNs) born before the 38th gestation week. Control group consisted of 123 full-term healthy new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Presence of the G allele at the AKAP10 locus is also associated with decreased preterm birth, however. A study of 203 newborns showed that preterm newborns were 55% more likely to be AA homozygotes than full term newborns, indicating a positive association between the G allele and full-term birth ( Łoniewska et al, 2012 ). Those authors suggested that newborns homozygous for the G allele may be more efficient at changing from glycolytic to oxidative metabolism after birth.…”
Section: Resultsmentioning
confidence: 99%
“…Presence of the G allele at the AKAP10 locus is also associated with decreased preterm birth, however. A study of 203 newborns showed that preterm newborns were 55% more likely to be AA homozygotes than full term newborns, indicating a positive association between the G allele and full-term birth ( Łoniewska et al, 2012 ). Those authors suggested that newborns homozygous for the G allele may be more efficient at changing from glycolytic to oxidative metabolism after birth.…”
Section: Resultsmentioning
confidence: 99%
“…The confounded association resulting from stratification or admixture within a population can be reduced by matching by geographical region and/or by markers of ethnic origin [36]. The population now inhabiting the region of West Pomerania resulted from extensive mixing of Polish people from all regions of Poland after the Second World War and therefore can provide a representative sample of a Caucasian-European population [37]. In addition, the rs7922846 allele frequencies were similar to those reported in adult control subjects in a Leipzig cohort, a self-contained Sorbian population in Germany [16], and Utah residents with ancestry from Northern and Western Europe from the HapMap project [38].…”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of an exon 5 variant, a population group (100 Polish newborns randomly chosen from the Newborn DNA Repository at the Department of Clinical and Molecular Biochemistry at the Pomeranian Medical University in Szczecin [17]) was screened by sequencing exon 5.…”
Section: Introductionmentioning
confidence: 99%